Phylogeny and nitrogen fixation potential of Bradyrhizobium species isolated from the legume cover crop Pueraria phaseoloides (Roxb.) Benth. in Eastern Cameroon - Sarr, S.; Araki, S.; Begoude, A.; Yamakawa, T.; Manga, G.A.; Htwe, A.Z. (Informa UK Limited, 2016)
Pueraria is an herbaceous, perennial legume crop originating in Asia. Pueraria phaseoloides (Roxb.) Benth. (tropical kudzu) is frequently introduced into production systems and is used as green manure, a cover crop and a forage plant, making it important economically. We used P. phaseoloides as a trap crop to study and characterize soil rhizobia in Eastern Cameroon. Bacteria were isolated from fresh nodules collected from field-grown P. phaseoloides roots. The 16S-23S rRNA internal transcribed spacer (ITS) sequences from 30 bacterial isolates were amplified by polymerase chain reaction (PCR) and the reaction products were sequenced. Phylogenetic analysis revealed that all isolates were ascribed to the genus Bradyrhizobium and were grouped into three clusters of Bradyrhizobium sp. strains, one cluster of B. yuanmingense strains, and one cluster of B. elkanii strains. Acetylene reduction assay (ARA) results indicated that the B. yuanmingense strains had significantly higher nitrogen fixation potential and that they could be used as inoculants to enhance nitrogen fixation in Pueraria grown in Eastern Cameroon.